BENEFITS OF LITHIUM MINING TO NIGERIA’S ECONOMIC DEVELOPMENT - CLINTON, EBIKEMEFA EBIMOBOWEI; BASU, MARTINS (Innovare Journal of Social Sciences, 2024)
Lithium mining goes beyond the extraction of lithium ore; it involves the technological importance of the mineral together with its application. This refers to eco-friendly applications such as the production of electric cars, the production of lithium batteries for solar panels, and other electrical devices. Obtained lithium (spodumene) samples from visited mine sites in Gidan Kwano (Nasarawa State), Kokona (Nasarawa State), and Takushara (Abuja-Kuje LGA) were taken to the laboratory for analysis. The atomic absorption spectrometry result shows a lithium percentage that ranges from 1% to 4.5% (low to high grade). A statistical analysis of data for total production of lithium in a month (through interactive sessions with miners on-site) shows that over 20 tons of lithium can be produced in a month by an active lithium mine site. Conclusively, if 20 tons is used as the benchmark, this means that a total of 40 trucks worth ₦20,375,000,000 will be made per month and a total of ₦244,500,000,000 per year. With this amount of money, after the removal of various royalties, it can go a long way in handling various issues in the state, local government, and even at the federal level. Well-monitored lithium mining can create jobs for indigenous people in the community, and the financial contribution can increase the internally generated revenue. The production of electric cars in Nigeria will also help solve the issue of carbon emissions and create a friendly eco-system.